Composite RNA aptamers as functional mimics of proteins - Xu, Daiying (Oxford University Press, 2009)
Individual RNA aptamers are often used to modulate the function of their target proteins, and multi-valent aptamers have been constructed to enhance their activity. To expand the utility of aptamers in manipulating and controlling biological processes, here we advance a general method for the design and construction of composite aptamers. The resulting molecular constructs resemble proteins in that they can form specific interactions with three or more different partners and be readily integrated into existing protein regulatory networks. As the first embodiment of this method, we created a tetra-valent aptamer that simultaneously binds to two molecules of the Drosophila protein B52 and two copies of streptavidin, thus mimicking the function of an antibody in immunochemical assays. We demonstrated that the performance of this ‘aptabody’ rivals that of a monoclonal antibody against B52 in these assays. While this study was performed in vitro and the composite aptamer we made was intended to mimic an existing protein, the same method can be used to accommodate arbitrary combinations of individual aptamers in composite molecular contexts, and these constructs can be delivered into living cells, where they are able to utilize existing cellular infrastructure for their production and processing.